Bloodlines: mammals, leeches, and conservation in southern Asia. Issue 5 (4th July 2018) - Tessler, Michael; Weiskopf, Sarah R.; Berniker, Lily; Hersch, Rebecca; Mccarthy, Kyle P.; Yu, Douglas W.; Siddall, Mark E.
Abstract : Southern Asia is a biodiversity hotspot both for terrestrial mammals and for leeches. Many small-mammal groups are under-studied in this region, while other mammals are of known conservation concern. In addition to standard methods for surveying mammals, it has recently been demonstrated that residual bloodmeals within leeches can be sequenced to find mammals in a given area. While these invertebrate-parasite-derived DNA (iDNA) methods are promising, most of the leech species utilized for this type of survey remain unevaluated, notwithstanding that their diversity varies substantially. Here we examine approximately 750 individual leech specimens in the genus Haemadipsa across a large range in southern Asia (Bangladesh, Cambodia, and China), specifically reviewing the diversity of mammals they feed on and their own genetic structuring. Leeches were found to feed on a considerable variety of mammals, corroborating prior studies. Additionally, leeches were found to have fed both on bats and on birds, neither of which has previously been recorded with this method. The genetic structuring of the leeches themselves revealed 15 distinct clades of which only two precisely corresponded to previously characterized species, indicating that much work is needed to finalize classifications in this genus. Most importantly, with regards to mammal conservation, leeches in these clades appear to feed on a broad range of mammals.